THE OBLIGATION OF PARIS AGREEMENT 2015 IN REDUCING CARBON EMISSIONS (A CASE STUDY IN PT. SOLUSI BANGUN ANDALAS) - Hasz, M. Ofans; Roesa, Nellyana (Student Journal of International Law, 2022)
This paper aims to find out the roles of corporate responsibility in reducing carbon emissions under international law, and to find out the carbon emission reduction programs carried out by PT. Solusi Bangun Andalas (SBA) as a form of corporate responsibility. This paper uses primary data obtained in field in the form of interviews with respondents and informants, observations, and combines legal materials such as textbooks, theories, laws and regulations which become secondary data. The results found that the Paris Agreement is one of the most likely solutions in the future in terms of order to deal with the impact of climate change, especially in terms of reducing carbon emissions due to the firmness of including to hold global temperatures below 2 degrees Celsius, and also to overcome the increase in carbon emissions.